Aetion, Artist of the Age of Alexander - Corso, Antonio (Actual Problems of Theory and History of Art, 2017)
The article focuses on the important artist Aetion who flourished in the 4th century BC. This painter and sculptor has never been the specific object of scholarly concern but a detailed study allows an outline of his life as well as to reach an idea of at least a few of his works. He was born at Amphipolis, his main work of his youth may have been his triad of Dionysus, Comedy and Tragedy. This creation may have been copied with the statue of these three subjects from the sanctuary of Dionysus on Thasos, not far away from Amphipolis.The turning moment of his life must have been the year 324 BC, when he took part in the competition of painters held at Olympia, where the Hellanodikoi decided the winner. He won and married the daughter of the president of this powerful college. Moreover, the subject of his winning picture — the Wedding of Rhoxane and Alexander — may have introduced Aetion to the royal circle of Macedon. This picture became very famous andmay have inspired a wall painting on Delus. Finally, Aetion may have been the artist responsible for sculptures and paintings of tumulus Kasta near Amphipolis, to be dated around 320 BC. The Sphinxes and Karyatids of this tumulus look stylistically very close to Dionysus and Comedy from Thasos. Moreover, the paintings in this tumulus are still the work of a painter who uses only the canonic four colors of the tradition and we know that Aetion was a tetrachromatic. Finally, an epigram describing a figure by this artist fits well the relief on the base of the lion above this tumulus.
Keywords: Amphipolis; Thasos; Aetion; Rhoxane; Alexander; Dionysus; tragedy; comedy